Free Family Planning Service In Rt 24 Of Sawah Lebar Urban Village, Ratu Agung Sub-District, Kota Bengkulu - Anggi Pratiwi, Nindya; Invaka, Vela; Hadara, Hadara; Furiyanti, Murdani; Dwi Tania, Rilda; Tri Prasetyo, Lupus; Kembang Sari, Delvi; Yuliani Y, Reza; Kurniawan Sari, Helpi; Ramdan, Asrial; Aurosi, Miftakhul; Yovita Sari, Lezi; Wara, Gina (Universitas Dehasen Bengkulu, 2024)
The family planning program provides the opportunity to space out or reduce the number of births by using contraceptive methods. The general goal of this program is to identify the problem of low contraceptive coverage and improve the skills and knowledge of the community in Sawah Lebar Subdistrict RT 24. The specific objectives include geographical and demographic mapping of the area, data collection and assessment of family planning issues, and conducting monitoring and evaluation of the activity results.This activity is carried out by providing information about family planning and offering free family planning services to 20 WUS (Women of Reproductive Age) family planning acceptors in the Sawah Lebar area. The results of this free family planning service are followed by providing evaluations to the acceptors through Q&A sessions about family planning and monitoring and evaluation. Family planning participants were able to answer and explain the questions well and were willing to use IUD or Implant contraceptives. The activities conducted went well. Family planning participants in the Sawah Lebar area showed enthusiasm in participating in the activities.